(untitled) (Global Journal of Human-Social Science, 2010)
The study assessed farmer’s perception of impact of climate change on food crop production in Ogbomoso Agricultural zone of Oyo State, Nigeria. It highlights the socioeconomic characteristics of the farmers, farmer’s perception on climate change, impact of climate change on crop production and adaptation strategies adopted to mitigate the effect of climate change. Data were collected by using structured interview schedule administered on 360 farmers randomly selected from the three agricultural extension blocks in the study area. Description and analysis of data were carried out using frequency counts, percentages means and tables, while multiple regression was used to test the hypothesis. About 72.0% of the respondents were male, and 95.8% were between 31 and above 51 years old. While 29.4% had no formal education,70.6% have various levels of formal education. About 90% of the farmers had many years of farming experience ranging from6years to 21years and above. Only 31.1% and 24.7% of the respondents indicated delayed rainfall and higher temperature respectively as their perception of climate change. About 12% indicated unusual heavy rainfall, 9.4% indicated undefined season, while 4.4% and 4.2% respectively indicated flood with serious consequences and later fruiting of tree crops respectively as their perception of climate change. About 80.3% of the respondents mentioned low yield of crops as the impact of climate change on crop production, stunted growth (37.2%), ease spread of pest and diseases attack on crops (31.1%). Even though only 68.3% indicated increased water conservation as adaptation strategies, 74.7% mentioned planting of different crops while 54.4% change row orientation with respect to slope, as the adaptation strategies to mitigate impact of climate changes. A significant relationship at 0.05 significant level with coefficient of (R 2 = 0.612) was found between perceived climate change and adaptation strategies. Therefore Arable food crop farmers are more knowledgeable of climate change and even its impacts on their livelihood that should be considered in policy formulation on adaptation of agricultural production systems to climate change.